Orbital character and electron correlation effects on two- and three-dimensional Fermi surfaces in KFe2As2 revealed by angle-resolved photoemission spectroscopy - Yoshida, Teppei; Ideta, Shin-ichiro; Nishi, Ichiro; Fujimori, Atsushi; Yi, Ming; Moore, Rob; Mo, Sung-Kwan; Lu, Donghui; Shen, Zhi-Xun; Hussain, Zahid; Kihou, Kunihiro; Lee, C. H; et al. (Frontiers in Physics, 2014)
We have investigated orbital character and electron correlation effects on Fermi surfaces in the hole-overdoped iron pnictide superconductor KFe2As2, which shows a low Tc of 4 K, by angle-resolved photoemission spectroscopy. From the polarization-dependence of the ARPES spectra, we have determined the orbital character of each Fermi surface. Electron mass renormalization of each band is quantitatively consistent with de Haas-van Alphen results. The outer β and middle ζ Fermi surfaces show large renormalization factor of m*/mb 6–7, while the inner α Fermi surface has a smaller factor m*/mb 2. Middle hole Fermi surface ζ has strong three-dimensionality compared to other Fermi surfaces, indicating the d3z2–r2 orbital character, which may be related to the “octet-line nodes” recently observed by laser ARPES. The observed orbital-dependent mass renormalization would give constraints on the pairing mechanism with line nodes of this system.